Effects of a stress management intervention on salivary cortisol during competition of western performance equestrians - A. Baxter; J.L. Zoller; C.J. Huseman; J. Ripley; L. Colvin; P. Linne (Journal of Equine Veterinary Science, 2025)

Estimating the trapping area and density of common whelk (Buccinum undatum) using experimental fishing - Matthew J. Garratt; Isobel S.M. Bloor; Matthew T. Coleman; Charlotte N. Colvin; Jan Geert Hiddink; Natalie Hold; Stuart R. Jenkins (Fisheries Research, 2025)

Effects of snake fungal disease (ophidiomycosis) on the skin microbiome across two major experimental scales - Alexander S. Romer; Matthew Grisnik; Jason W. Dallas; William Sutton; Christopher M. Murray; Rebecca H. Hardman; Tom Blanchard; Ryan J. Hanscom; Rulon W. Clark; Cody Godwin; N. Reed Alexander; Kylie C. Moe; et al. (Conservation Biology, 2025)
Emerging infectious diseases are increasingly recognized as a significant threat to global biodiversity conservation. Elucidating the relationship between pathogens and the host microbiome could lead to novel approaches for mitigating disease impacts. Pathogens can alter the host microbiome by inducing dysbiosis, an ecological state characterized by a reduction in bacterial alpha diversity, an increase in pathobionts, or a shift in beta diversity. We used the snake fungal disease (SFD; ophidiomycosis), system to examine how an emerging pathogen may induce dysbiosis across two experimental scales. We used quantitative polymerase chain reaction, bacterial amplicon sequencing, and a deep learning neural network to characterize the skin microbiome of free‐ranging snakes across a broad phylogenetic and spatial extent. Habitat suitability models were used to find variables associated with fungal presence on the landscape. We also conducted a laboratory study of northern watersnakes to examine temporal changes in the skin microbiome following inoculation with Ophidiomyces ophidiicola . Patterns characteristic of dysbiosis were found at both scales, as were nonlinear changes in alpha and alterations in beta diversity, although structural‐level and dispersion changes differed between field and laboratory contexts. The neural network was far more accurate (99.8% positive predictive value [PPV]) in predicting disease state than other analytic techniques (36.4% PPV). The genus Pseudomonas was characteristic of disease‐negative microbiomes, whereas, positive snakes were characterized by the pathobionts Chryseobacterium , Paracoccus , and Sphingobacterium . Geographic regions suitable for O. ophidiicola had high pathogen loads (>0.66 maximum sensitivity + specificity). We found that pathogen‐induced dysbiosis of the microbiome followed predictable trends, that disease state could be classified with neural network analyses, and that habitat suitability models predicted habitat for the SFD pathogen.

Effects of disturbance on macrofaunal biodiversity‐ecosystem functioning relationships in seagrass habitats - T. J. Colvin; P. V. R. Snelgrove (Marine Ecology, 2023)
Seagrass beds support diverse macrofaunal communities, and collectively they influence carbon and nutrient cycles; however, we know little on how seagrass disturbance alters this relationship. In Newfoundland, Canada, the invasive European green crab Carcinus maenas threatens the seagrass Zostera marina by snipping and uprooting seagrasses while foraging and burrowing. In order to understand the effects of seagrass disturbance on macrofaunal diversity and ecosystem functioning within sediments, we experimentally uprooted small patches of seagrass and compared rates of oxygen and nutrient fluxes from sediment cores from uprooted (disturbed) patches, seagrasses, and unvegetated sediments nearby. In parallel, we assessed macrofaunal biodiversity (taxonomic and functional) and sedimentary (granulometric properties and organic matter content/freshness) variables in all three of these treatments over a three‐month period. As expected, macrofaunal abundance, species richness and functional richness declined significantly initially in disturbed cores, although this decrease had little effect on benthic flux rates. Over 3 months, macrofaunal colonization of the disturbed sediments resulted in abundances similar to the natural seagrass and unvegetated treatments. We also observed a change in nutrient flux rates that we attribute to seasonal shifts in regeneration pathways rather than macrofaunal community recovery, suggesting a lesser role for macrofaunal diversity in carbon and nutrient cycling in dynamic nearshore habitats than in deeper water. Our results demonstrate the impacts of green crab‐mediated seagrass disturbance on macrofaunal abundance and community structure while highlighting their potential capacity for rapid stabilization, and emphasize the strength of large‐scale seasonal environmental changes on ecosystem processes.

A Meta-Analysis of the Genome-Wide Association Studies on Two Genetically Correlated Phenotypes Suggests Four New Risk Loci for Headaches - Weihua Meng; Parminder S. Reel; Charvi Nangia; Aravind Lathika Rajendrakumar; Harry L. Hebert; Qian Guo; Mark J. Adams; Hua Zheng; Zen Haut Lu; Debashree Ray; Lesley A. Colvin; Colin N. A. Palmer; et al. (Phenomics, 2023)
Headache is one of the commonest complaints that doctors need to address in clinical settings. The genetic mechanisms of different types of headache are not well understood while it has been suggested that self-reported headache and self-reported migraine were genetically correlated. In this study, we performed a meta-analysis of genome-wide association studies (GWAS) on the self-reported headache phenotype from the UK Biobank and the self-reported migraine phenotype from the 23andMe using the Unified Score-based Association Test (metaUSAT) software for genetically correlated phenotypes ( N = 397,385). We identified 38 loci for headaches, of which 34 loci have been reported before and four loci were newly suggested. The LDL receptor related protein 1 ( LRP1 )— Signal Transducer and Activator of Transcription 6 ( STAT6 )— S hort chain D ehydrogenase / R eductase family 9C member 7 ( SDR9C7 ) region in chromosome 12 was the most significantly associated locus with a leading p value of 1.24 × 10 –62 of rs11172113. The One Cut homeobox 2 ( ONECUT2 ) gene locus in chromosome 18 was the strongest signal among the four new loci with a p value of 1.29 × 10 –9 of rs673939. Our study demonstrated that the genetically correlated phenotypes of self-reported headache and self-reported migraine can be meta-analysed together in theory and in practice to boost study power to identify more variants for headaches. This study has paved way for a large GWAS meta-analysis involving cohorts of different while genetically correlated headache phenotypes.

Growth, reproduction, and age at maturity of Lessa’s butterfly ray Gymnura lessae in the northern Gulf of Mexico - Matthew B. Jargowsky; Bryan L. Huerta-Beltrán; Matthew J. Ajemian; Michael E. Colvin; J. Marcus Drymon (Environmental Biology of Fishes, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Estimates of environmental loading from copper alloy materials - Patrick J. Earley; Brandon L. Swope; Marienne A. Colvin; Gunther Rosen; Pei-Fang Wang; Jessica Carilli; Ignacio Rivera-Duarte (Biofouling, 2020)

Discerning the dietary habits of the smooth butterfly ray Gymnura lessae using two distinct methods, otolith identification and metagenetics - Matthew B. Jargowsky; Pearce T. Cooper; Matthew J. Ajemian; Michael E. Colvin; J. Marcus Drymon (Journal of Fish Biology, 2020)
Two different methods, metagenetics and free‐otolith identification, were used to identify prey in the stomach contents of 531 Gymnura lessae captured by trawling in Mobile Bay, Alabama 2016–2018. Both methods were found to produce analogous results and were therefore combined into a single complete dataset. All prey were teleosts; the families Sciaenidae and Engraulidae were the most important prey (prey specie index of relative importance 89.3% I PSRI ). Multivariate analyses indicated that the diet of G. lessae varied with sex and seasonality. Specifically, variability was probably due to morphologically larger females consuming larger teleost prey species compared with males, whereas seasonal variability was probably due to changes in the available prey community composition. The findings indicate that both metagenetics and free otolith identification, used independently or complementarily, offer robust means of characterising dietary habits for teleost‐specialised species such as G. lessae , which may play an important role in the structure and maintenance of coastal food webs such as those in Mobile Bay.

Dietary plasticity in a nutrient-rich system does not influence brown bear (Ursus arctos) body condition or denning - Lindsey S. Mangipane; Jerrold L. Belant; Diana J. R. Lafferty; David D. Gustine; Tim L. Hiller; Michael E. Colvin; Buck A. Mangipane; Grant V. Hilderbrand (Polar Biology, 2018)

Nickel and Copper Toxicity to Embryos of the Long-Spined Sea Urchin, Diadema savignyi - G. Rosen; I. Rivera-Duarte; M. A. Colvin; R. E. Dolecal; L. J. Raymundo; P. J. Earley (Bulletin of Environmental Contamination and Toxicology, 2015)

Pharmacological characterisation of ligand- and voltage-gated ion channels expressed in human iPSC-derived forebrain neurons - Jeffrey L. Dage; Ellen M. Colvin; Antoine Fouillet; Emily Langron; William C. Roell; Jingling Li; Sachin X. Mathur; Adrian J. Mogg; Matthew G. Schmitt; Christian C. Felder; Kalpana M. Merchant; John Isaac; et al. (Psychopharmacology, 2014)

The Pel and Psl polysaccharides provide Pseudomonas aeruginosa structural redundancy within the biofilm matrix - Kelly M. Colvin; Yasuhiko Irie; Catherine S. Tart; Rodolfo Urbano; John C. Whitney; Cynthia Ryder; P. Lynne Howell; Daniel J. Wozniak; Matthew R. Parsek (Environmental Microbiology, 2012)
Summary Extracellular polysaccharides comprise a major component of the biofilm matrix. Many species that are adept at biofilm formation have the capacity to produce multiple types of polysaccharides. Pseudomonas aeruginosa produces at least three extracellular polysaccharides, alginate, Pel and Psl, that have been implicated in biofilm development. Non‐mucoid strains can use either Pel or Psl as the primary matrix structural polysaccharide. In this study, we evaluated a range of clinical and environmental P. aeruginosa isolates for their dependence on Pel and Psl for biofilm development. Mutational analysis demonstrates that Psl plays an important role in surface attachment for most isolates. However, there was significant strain‐to‐strain variability in the contribution of Pel and Psl to mature biofilm structure. This analysis led us to propose four classes of strains based upon their Pel and Psl functional and expression profiles. Our data also suggest that Pel and Psl can serve redundant functions as structural scaffolds in mature biofilms. We propose that redundancy could help preserve the capacity to produce a biofilm when exopolysaccharide genes are subjected to mutation. To test this, we used PAO1, a common lab strain that primarily utilizes Psl in the matrix. As expected, a psl mutant strain initially produced a poor biofilm. After extended cultivation, we demonstrate that this strain acquired mutations that upregulated expression of the Pel polysaccharide, demonstrating the utility of having a redundant scaffold exopolysaccharide. Collectively, our studies revealed both unique and redundant roles for two distinct biofilm exopolysaccharides.

Pollution magnet: nano-magnetite for arsenic removal from drinking water - Cafer T. Yavuz; J. T. Mayo; Carmen Suchecki; Jennifer Wang; Adam Z. Ellsworth; Helen D’Couto; Elizabeth Quevedo; Arjun Prakash; Laura Gonzalez; Christina Nguyen; Christopher Kelty; Vicki L. Colvin (Environmental Geochemistry and Health, 2010)

PCR-based detection and partial genome sequencing indicate high genetic diversity in Bangladeshi begomoviruses and their whitefly vector, Bemisia tabaci - M. N. Maruthi; A. R. Rekha; S. H. Mirza; S. N. Alam; J. Colvin (Virus Genes, 2007)

Diversity and distribution of begomoviruses infecting tomato in India - R. V. Chowda Reddy; J. Colvin; V. Muniyappa; S. Seal (Archives of Virology, 2005)

Bionomics, morphometrics and molecular characterization of a cassava Bemisia afer (Priesner & Hosny) population - M.N. Maruthi; S. Navaneethan; John Colvin; Rory J. Hillocks (International Journal of Tropical Insect Science, 2004)

East African cassava mosaic Zanzibar virus – a recombinant begomovirus species with a mild phenotype - M. N. Maruthi; S. Seal; J. Colvin; R. W. Briddon; S. E. Bull (Archives of Virology, 2004)

RHYTHMICITY OF ENGRAFTMENT AND ALTERED CELL CYCLE KINETICS OF CYTOKINE-CULTURED MURINE MARROW IN SIMULATED MICROGRAVITY COMPARED WITH STATIC CULTURES - GERALD A. COLVIN; JEAN-FRANÇOIS LAMBERT; JANE E. CARLSON; CHRISTINA I. McAULIFFE; MEHRDAD ABEDI; PETER J. QUESENBERRY (In Vitro Cellular & Developmental Biology - Animal, 2002)